Effectiveness of Flavonoid (Moringa oleifera) as an Anti-inflammatory: Efektivitas Flavonoid (Moringa oleifera) sebagai Anti-inflamasi - Dewi Ni Luh Made Noviana; Ketut Suniartini; I Nyoman Sridana (Widya Kesehatan, 2025)
Background: Inflammation is the body's response to injury due to infection by antigens or cell damage, indicating that something harmful or painful is present in the body. Inflammation is also a protective response to cell damage or infection. Currently, the development of traditional medicine in Indonesia is a hot topic of discussion. With the rapid advancement of technology, many people are affected by various diseases such as inflammation, and so on. Moringa leaves have anti-inflammatory properties. Flavonoids have antioxidant properties that inhibit the development of free radicals. Objective: The objective of this study is to conduct a literature review to gather general information about the use of Moringa oleifera Lamk and the role of flavonoids in inflammation. Method: This article review was compiled using a comparative and search method from various sources such as (Google, Google Scholar, NCBI, PubMed) in the period 2020-2025. Results: Based on the literature review, it can be concluded that the use of moringa leaves (Moringa oleifera) has a significant effect on inflammation. This is due to the flavonoid content in moringa leaves, which has anti-inflammatory properties. Conclusion: Moringa leaves have many benefits, so it is recommended to increase consumption of these leaves.